2013
DOI: 10.1038/ejhg.2013.86
|View full text |Cite
|
Sign up to set email alerts
|

Platelet defects in congenital variant of Rett syndrome patients with FOXG1 mutations or reduced expression due to a position effect at 14q12

Abstract: The Forkhead box G1 (FOXG1) gene encodes a transcriptional repressor essential for early development of the telencephalon. Intragenic mutations and gene deletions leading to haploinsufficiency cause the congenital variant of Rett syndrome. We here describe Rett syndrome-like patients, three of them carrying a balanced translocation with breakpoint in the chromosome 14q12 region, and one patient having a 14q12 microdeletion excluding the FOXG1 gene. The hypothesis of long-range FOXG1-regulatory elements in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 52 publications
(74 reference statements)
0
14
0
Order By: Relevance
“…No increased clinical bleeding tendency has been reported in these patients, but it was recently shown that platelets from these patients have decreased responses to epinephrine and abnormal granules. 77 These data suggest a non-transcriptional role of FOXG1 in the amplification of intracellular signal transduction after initial platelet activation.…”
Section: Defects In Transcription Factor Foxgimentioning
confidence: 87%
See 1 more Smart Citation
“…No increased clinical bleeding tendency has been reported in these patients, but it was recently shown that platelets from these patients have decreased responses to epinephrine and abnormal granules. 77 These data suggest a non-transcriptional role of FOXG1 in the amplification of intracellular signal transduction after initial platelet activation.…”
Section: Defects In Transcription Factor Foxgimentioning
confidence: 87%
“…76 Genes for some transcription factors, such as the forkhead box G1 (FOXG1) gene, are expressed in both platelets and neurons. 77 FOXG1 encodes a transcriptional repressor that is important for prenatal development of the ventral telencephalon by integrating several brain signalling centres. 78 Postnatally, FOXG1 promotes postmitotic neuronal cell survival.…”
Section: Defects In Transcription Factor Foxgimentioning
confidence: 99%
“…e | Balanced translocations at the MEF2C locus cause a regulator loss of function and are associated with anomalies of the brain (including callosum hypoplasia 142 ) and developmental delay 116 . For examples see REFS 99,104,143 . PRS, element associated with Pierre Robin sequence; RevSex, element associated with disorders of sex development.…”
Section: Intra-tad Svs: Effects On Enhancer Dosagementioning
confidence: 99%
“…Of particular interest was the breakpoint located in 14q12, which fell amidst other rearrangement positions in association with RTT-like phenotypes and reportedly affecting FOXG1 function (Fig. 3) [4,[22][23][24]54]. Exome analysis by the DDD project ruled out the contribution of variants in known RTT genes (including methyl-CpG binding protein 2 (MECP2)) leading to the As demonstrated in other studies [4,[16][17][18][19][20]55], TAD disruption may affect expression of genes located within the domain by disrupting long-range promoter/enhancer interactions.…”
Section: Resultsmentioning
confidence: 99%